2015
DOI: 10.18632/oncotarget.3276
|View full text |Cite
|
Sign up to set email alerts
|

Novel harmine derivatives for tumor targeted therapy

Abstract: Harmine is a beta-carboline alkaloid found in medicinal plant PeganumHarmala, which has served as a folk anticancer medicine. However, clinical applications of harmine were limited by its low pharmacological effects and noticeable neurotoxicity. In this study, we modified harmine to increase the therapeutic efficacy and to decrease the systemic toxicity. Specifically, two tumor targeting harmine derivatives 2DG-Har-01 and MET-Har-02 were synthesized by modifying substituent in position-2, -7 and -9 of harmine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…To improve the therapeutic efficacy of 59, several derivatives were synthesized by modification of substituents in positions 2, 7, and 9 of harmine (59) ring and with other two different groups-2-amino-2-deoxy-D-glucose and methionine-two derivatives were obtained, 2DG-Har-01 (60) and MET-Har-02 (61), respectively. This study found that substitution at position 7 reduced natural toxicity and increased tumor cell uptake ability, at position 9 enhanced cytotoxicity, and at position 2 enhanced the antiproliferative effect [132], and also showed that substituents at position 1 could be crucial to antitumor potency [136]. SAR studies confirmed that substituents in position 2 and 9 displayed an important role in modulation of antitumor activities [134].…”
Section: Harmine and Derivativesmentioning
confidence: 64%
See 4 more Smart Citations
“…To improve the therapeutic efficacy of 59, several derivatives were synthesized by modification of substituents in positions 2, 7, and 9 of harmine (59) ring and with other two different groups-2-amino-2-deoxy-D-glucose and methionine-two derivatives were obtained, 2DG-Har-01 (60) and MET-Har-02 (61), respectively. This study found that substitution at position 7 reduced natural toxicity and increased tumor cell uptake ability, at position 9 enhanced cytotoxicity, and at position 2 enhanced the antiproliferative effect [132], and also showed that substituents at position 1 could be crucial to antitumor potency [136]. SAR studies confirmed that substituents in position 2 and 9 displayed an important role in modulation of antitumor activities [134].…”
Section: Harmine and Derivativesmentioning
confidence: 64%
“…This study found that substitution at position 7 reduced natural toxicity and increased tumor cell uptake ability, at position 9 enhanced cytotoxicity, and at position 2 enhanced the antiproliferative effect [132], and also showed that substituents at position 1 could be crucial to antitumor potency [136]. SAR studies confirmed that substituents in position 2 and 9 displayed an important role in modulation of antitumor activities [134].…”
Section: Harmine and Derivativesmentioning
confidence: 64%
See 3 more Smart Citations